Safety and efficacy of endovascular patent foramen ovale closure: the first results of a Russian multicenter study - D. V. Ognerubov; A. S. Tereshchenko; A. N. Samko; G. К. Arutyunyan; O. A. Sivakova; D. V. Pevzner; M. I. Makeev; T. V. Balakhonova; A. V. Belopasova; M. Yu. Maksimova; S. E. Chuprina; E. P. Khodyakova; et al. (Неврология, нейропсихиатрия, психосоматика, 2020)
Patent foramen ovale (PFO) is detectable in more than 25% of the adult population and is generally clinically insignificant. However, it can be a cause of paradoxical embolism in some cases. Randomized trials indicate that endovascular PFO closure in patients with a history of cryptogenic stroke is an effective method for the secondary prevention of catastrophic brain damage.Objective: to study the safety and efficiency of endovascular PFO closure in young patients with a history of cryptogenic stroke.Patients and methods. Sixty-two patients, including (22 males and 40 females) women, underwent percutaneous PFO closure in May 2018 to March 2020. The patients' mean age was 37.4±7.6 years. The inclusion criteria were a prior cryptogenic ischemic stroke lasting less than 12 months and PFO with a high risk for paradoxical embolism (PFO concurrent with atrial septal aneurysm or hypermobility; PFO, ≥2 mm size; the presence of the Chiari network and/or the Eustachian valve).Results and discussion. The technical success of the operation was achieved in all cases. In 50 (80.6%) patients, the right chamber of the heart was completely isolated from the left one in the first 3 months. During the first year, the atria were also completely isolated in 10 (16.1%) patients. A left-to-right shunt persisted in 2 (3.2%) patents 12 months later. Two patients were found to have main procedural complications: one had perioperative atrial fibrillation and the other had pseudoaneurysm formation at the puncture site.Conclusion. Endovascular PFO closure is a safe and effective operation for the secondary prevention of recurrent ischemic stroke. In our study, blood shunting through the PFO was stopped in 96.6% of patients at less than 6 months after surgery, which suggests that there is a rapid and effective reduction in the risk of paradoxical embolism.